The asymptotic of the distribution of the maxima of the nonidentically distributed random variables - Jokimaitis, Arvydas (Lietuvos matematikos rinkinys, 2004)
In this paper the nonuniform estimate for the distribution of the maxima of the nonidentically distributed independent random variables is obtained.